2019
DOI: 10.1177/0091415019852777
|View full text |Cite
|
Sign up to set email alerts
|

Living Arrangements and Sleep-Related Outcomes Among Older Adults in China

Abstract: It has been discussed previously that older adults’ living arrangements are associated with mortality. This study investigated the relationships between older adults’ living arrangements and sleep-related outcomes in China. The nationally representative sample included 4,731 participants who participated on two different occasions, with a total of 9,462 observations (2012 and 2014 waves). Panel logistic regression and panel ordinary least squares regression models were estimated with outcomes of sleep quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 28 publications
2
14
0
Order By: Relevance
“…A study of middle-aged and older adults in Beijing and Shanghai, however, reported that only 19% of Beijing and 13% of Shanghai respondents experienced poor sleep quality (Haseli-Mashhadi et al, 2009). Estimates of sleep quality using nationally representative data showed that 62%-65% of Chinese older adults reported good quality of sleep (Gu et al, 2010;Lee et al, 2020). The discrepancies may be due to the fact that these studies focused on different regions of China, used different age criteria for defining old age, and utilized different measures of sleep quality (e.g., a single-item scale or the Pittsburgh sleep quality index scale).…”
Section: Sleep Quality Among Older Adults In Chinamentioning
confidence: 99%
See 1 more Smart Citation
“…A study of middle-aged and older adults in Beijing and Shanghai, however, reported that only 19% of Beijing and 13% of Shanghai respondents experienced poor sleep quality (Haseli-Mashhadi et al, 2009). Estimates of sleep quality using nationally representative data showed that 62%-65% of Chinese older adults reported good quality of sleep (Gu et al, 2010;Lee et al, 2020). The discrepancies may be due to the fact that these studies focused on different regions of China, used different age criteria for defining old age, and utilized different measures of sleep quality (e.g., a single-item scale or the Pittsburgh sleep quality index scale).…”
Section: Sleep Quality Among Older Adults In Chinamentioning
confidence: 99%
“…As such, relationships with adult children are crucial for older Chinese adults' well-being (Chen & Jordan, 2018a;Guo et al, 2018;Silverstein et al, 2006). Some studies examined living arrangements as a type of family support, and the results showed that Chinese older adults living with family members had better sleep quality compared to those who lived alone (Gu et al, 2010;Lee et al, 2020). However, a comprehensive examination of the association between parent-child relations and sleep among Chinese older adults is warranted.…”
mentioning
confidence: 99%
“…Therefore, we should be careful about drawing conclusions regarding the discrepancies among the three types of living arrangements. However, according to a study by Lee and colleagues examining the association between living arrangement and sleep among Chinese older adults [ 27 ], nearly 81% of the older adults lived with their household members. This could be the result of the traditional belief of filial piety in the Chinese culture that children have the responsibility to take care of their parents/grandparents.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, older adults living with family had a lower mortality rate than those living alone because the former received physical and psychological support in their daily care [ 26 ]. Older adults who lived with family also had higher odds of reporting better sleep quality than those who lived alone [ 27 ]. The literature gaps regarding living arrangements among older adults demonstrate the need for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Family environment is another factor associated with sleeping-related issues. Many studies have reported that people living alone have a poorer quality of sleep and shorter sleep duration daily compared with those who live with household members [ 8 , 9 , 10 ]. However, it is not clear whether the phenomenon of living alone is an influencing factor that worsens the quality of sleep, especially in older adults.…”
Section: Introductionmentioning
confidence: 99%